Marketing Strategies of Secondhand Fashion/Thrift Shop in Increasing Sales in Surabaya (A Study on Tebal.Id Store Surabaya) - Amanda Meiliya; Yanda Bara Kusuma (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The fashion industry is experiencing rapid development, which also encourages the emergence of thrift shopping trends as an alternative for people, especially young people, to get quality clothes at affordable prices. This study aims determine and analyze the marketing strategies carried out by used fashion business actors/thrift shop (Tebal.Id Surabaya) in increasing sales in Surabaya City. The method used is with a qualitative approach, this research analyzes how the combination of 4P marketing strategies (Product, Price, Place, and Promotion) contributes to increasing sales and strengthening brand awareness in the used fashion market. Data were obtained through in-depth interviews (owner, marketing division employees, and 2 customers), observation, and documentation, which were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the utilization of digital marketing strategies, interactive promotions through social media, and the application of competitive prices were able to increase consumer attractiveness and had a direct impact on increasing sales of Tebal.Id Surabaya.